Unregistered marriages in islamic law: Ensuring children's rights amidst legal validity - Sarkanto; Hari Widiyanto (Amorti: Jurnal Studi Islam Interdisipliner, 2024)
This study aims to analyze the validity of Unregistered marriages from the perspective of Islamic law and its impact on children's rights, focusing on the decision of the Singaraja Religious Court Number 17/Pdt.P/2024/PA.Sgr. Unregistered marriages, although valid in Islam, are not legally recognized by the state without official registration. This has various legal implications, especially for children's rights. Children from serial marriages often do not get alimony rights, inheritance rights, and official identity recognition. This study uses a normative legal approach with descriptive analysis to explore the phenomenon of Unregistered marriages and its impact on children's rights from the perspective of Islamic law and positive law in Indonesia. The study results show that the court's determination of a child's origin provides a legal and recognized status, allowing access to rights such as education, health, and inheritance. Awareness of married couples and policy support from the government is needed to protect children's rights and ensure better legal certainty.